THE HIDDEN MYSTRY BEHIND ESTRICTION OF VIRAL REPLICATION BY MUTATION OF THE INFLUENZA VIRUS MATRIX PROTEIN - Mishell, Dr. Heddan; Prethew, Dr.Rikalt (International Journal of Multidisciplinary Research and Studies, 2022)
The matrix protein (M1) of the influenza virus plays a vital role in viral assembly and encompasses a form of functions, including association with influenza virus ribonucleoproteins (RNP). The RNA-binding domains of M1 are mapped to 2 independent regions: a zinc finger motif at organic compound positions 148 to 162 and a series of basic amino-alkanoic acids. To further understand the role of the RNP-binding domain of M1 in viral assembly and replication, mutations within the coding sequences of RKLKR and therefore the zinc finger motif of M1 were constructed employing a PCR technique and introduced into wild-type influenza virus by reverse genetics. These results indicate that the RKLKR domain of the M1 protein plays a crucial role in viral replication. The genome of influenza a pandemic consists of eight distinct segments of negative-sense RNA coding for a minimum of 10 viral proteins, of which 3 are known to function as polymerases. The viral RNA, nucleoprotein (NP), and polymerases are closely related to the ribonucleo protein (RNP) (11, 18, 22). Matrix protein (M1) is found between the RNP and also the inner surface of the lipid envelope within the intact virion (1, 3, 33). Two major external glycoproteins, hemagglutinin (HA) and neuraminidase (NA), and a little protein, M2, which is a trans membrane channel are anchored within the viral envelope (20, 36). M1 isn’t only a necessary structural component of the virion but also participates in other steps during the replication of the influenza virus. During early infection, dissociation of M1 from RNP is required for entry of viral RNP into the cytoplasm of the host cell (4, 12, 21). Dissociation is triggered by the transport of H+ ions across the viral membrane by M2 (12, 19, 36). it’s been shown also that M1 is transported from the cytoplasm into the nucleus during early viral replication (27). Later within the replication cycle, the buildup of M1 within the cytoplasm is concomitant with the nuclear export of RNP (4, 5, 13, 16, 35). within the maturation of viral particles, the M1/NP ratio of viral particles influences the virion’s morphological features and therefore the infectivity of the released viruses (29). The interactions of M1 with RNP are studied extensively (2, 6, 26, 31, 33, 41). Two domains in M1 are shown to affect its association with RNA (41, 42). One RNA-binding domain, containing a zinc finger motif (148C-C—-H-H162), has been shown to keep company with zinc ions (7) and to inhibit viral replication (23). the opposite domain, residing during a palindromic stretch of basic amino acids (101-RKLKR-105), has been shown to bind viral RNA (8, 37, 42), fulfilling a prediction supported by X-ray crystallographic studies (34). This domain also is a nuclear localization signal (NLS) for M1 (40, 43), but its role in viral replication is a smaller amount certain. Although it’s been reported that under acidic conditions, M1 dissociates from RNP, leading to a discount in the transport of RNP from the nucleus to the cytosol (4), the biological significance Our recent studies demonstrate that viral RNP isn’t assembled within the absence of M1 (15).